Insertional mutagenesis of Brachypodium distachyon using the Tnt1 retrotransposable element. (23rd June 2020) - Nandety, Raja Sekhar; Serrani‐Yarce, Juan C.; Gill, Upinder S.; Oh, Sunhee; Lee, Hee‐Kyung; Zhang, Xinji; Dai, Xinbin; Zhang, Wenchao; Krom, Nick; Wen, Jiangqi; Zhao, Patrick X.; Mysore, Kirankumar S.
SUMMARY: Brachypodium distachyon is an annual C3 grass used as a monocot model system in functional genomics research. Insertional mutagenesis is a powerful tool for both forward and reverse genetics studies. In this study, we explored the possibility of using the tobacco retrotransposon Tnt1 to create a transposon‐based insertion mutant population in B. distachyon . We developed transgenic B. distachyon plants expressing Tnt1 (R0) and in the subsequent regenerants (R1) we observed that Tnt1 actively transposed during somatic embryogenesis, generating an average of 6.37 insertions per line in a population of 19 independent R1 regenerant plants analyzed. In seed‐derived progeny of R1 plants, Tnt1 segregated in a Mendelian ratio of 3:1 and no new Tnt1 transposition was observed. A total of 126 flanking sequence tags (FSTs) were recovered from the analyzed R0 and R1 lines. Analysis of the FSTs showed a uniform pattern of insertion in all the chromosomes (1–5) without any preference for a particular chromosome region. Considering the average length of a gene transcript to be 3.37 kb, we estimated that 29 613 lines are required to achieve a 90% possibility of tagging a given gene in the B. distachyon genome using the Tnt1 ‐based mutagenesis approach. Our results show the possibility of using Tnt1 to achieve near‐saturation mutagenesis in B. distachyon, which will aid in functional genomics studies of other C3 grasses. Significance Statement: Retrotransposable elements transpose from one position in the DNA to another during embryogenesis, causing mutations at the genomic landing site. Here we show that Tnt1, a retrotransposable element from tobacco, can transpose in a monocot plant, Brachypodium distachyon . Based on the analyses of Tnt1 insertions in B. distachyon, we estimated that 29 613 lines would be needed to achieve a 90% probability of tagging every gene in the B. distachyon genome.